Dispersal Propensity and Dispersal Distance Are Genetically Independent Traits in a Stream Salamander - Winsor H. Lowe; Brett R. Addis; Madaline M. Cochrane (Molecular Ecology, 2026)
Empirical understanding of dispersal evolution is limited, due in large part to the complexity of the dispersal process and the difficulty of quantifying dispersal directly. To move ahead, it may help to focus on universal dispersal traits: propensity—the discrete emigration response distinguishing dispersers from non‐dispersers—and distance. In particular, little is known about the evolution of dispersal distance, including whether it is an independent trait subject to selection. We used capture‐recapture data and single nucleotide polymorphism (SNP) genotypes from 1906 salamanders sampled over 10 years to test for independent genetic associations with dispersal propensity and distance. Gyrinophilus porphyriticus is a headwater specialist, and our data are from three hydrologically independent streams in New Hampshire. We quantified dispersal propensities and distances directly with recapture histories and we used principal component analysis of SNP genotypes to derive three orthogonal axes of genetic variation. Of 173 recaptured individuals, 81 were non‐dispersers and 92 were dispersers based on an empirically derived 3‐m threshold distinguishing dispersal from movements within an individual's home range. Dispersal distances ranged from 4 to 1248 m. Dispersal propensity and distance were significantly associated with different axes of genetic variation, indicating that these are independent traits capable of responding to different selective forces. More broadly, these results show that quantifying dispersal propensities and dispersal distances—and explicitly assessing interactions and trade‐offs between these traits—may help to advance understanding of dispersal evolution.

Pan‐Arctic Peatlands Have Expanded During Recent Warming - J. Handley; R. E. Fewster; T. G. Sim; S. Hodson; B. Parker; K. Crichton; D. Charman; K. Anderson; M. Garneau; M. Väliranta; D. W. Beilman; G. T. Swindles; et al. (Global Change Biology, 2026)
The fate of carbon stored in Arctic peatlands remains uncertain because of the complex nature of the effects of climate change on permafrost and peatland carbon cycling. Expansion and/or shrinkage of Arctic peatlands under climate change also remain unknown due to lack of ground data and difficulties detecting changes in the extent of these ecosystems, meaning that land surface model predictions currently inadequately quantify Arctic terrestrial carbon storage changes. Pan‐Arctic shifts in peatland extent would profoundly change the fate of carbon in the terrestrial Arctic. Here, we tackle this knowledge gap by answering three main questions: (a) has lateral expansion occurred in Arctic peatlands as a response to recent warming? (b) if so, how fast has this occurred? (c) how does the response vary regionally? To answer these, we collected a dataset (12 peatland sites, 91 peat cores) combining peat cores collected across two latitudinal (north–south) transects: one in the European Arctic and one in the Canadian Arctic. In each region, we selected three peatland sites, with cores collected from transects spanning the peat‐edge to the peat‐centre. Our large‐scale dataset shows that peatlands have expanded, often rapidly, with some rates exceeding ~1 m per year since 1950 AD. This rapid expansion has occurred during a period of widespread Arctic warming and is still ongoing: two thirds (8/12) of our peatland sites evidence new peat formation after ~1990 AD based on age‐depth models constrained by 14 C and 210 Pb dating. Given that our sites comprise a broad range of Arctic conditions, we expect peatland expansion to be a pan‐Arctic phenomenon. Within specific regions, there are constraints on peat expansion including topographical limits, but we present the basis for future work to estimate pan‐Arctic peatland expansion, plus the associated carbon cycle implications under future climate change.

Outbreeding reduces survival during metamorphosis in a headwater stream salamander - Winsor H. Lowe; Brett R. Addis; Madaline M. Cochrane (Molecular Ecology, 2024)
Assessing direct fitness effects of individual genetic diversity is challenging due to the intensive and long‐term data needed to quantify survival and reproduction in the wild. But resolving these effects is necessary to determine how inbreeding and outbreeding influence eco‐evolutionary processes. We used 8 years of capture–recapture data and single nucleotide polymorphism genotypes for 1906 individuals to test for effects of individual heterozygosity on stage‐specific survival probabilities in the salamander Gyrinophilus porphyriticus . The life cycle of G. porphyriticus includes an aquatic larval stage followed by metamorphosis into a semi‐aquatic adult stage. In our study populations, the larval stage lasts 6–10 years, metamorphosis takes several months, and lifespan can reach 20 years. Previous studies showed that metamorphosis is a sensitive life stage, leading us to predict that fitness effects of individual heterozygosity would occur during metamorphosis. Consistent with this prediction, monthly probability of survival during metamorphosis declined with multi‐locus heterozygosity (MLH), from 0.38 at the lowest MLH (0.10) to 0.06 at the highest MLH (0.38), a reduction of 84%. Body condition of larvae also declined significantly with increasing MLH. These relationships were consistent in the three study streams. With evidence of localised inbreeding within streams, these results suggest that outbreeding disrupts adaptations in pre‐metamorphic and metamorphic individuals to environmental gradients along streams, adding to evidence that headwater streams are hotspots of microgeographic adaptation. Our results also underscore the importance of incorporating life history in analyses of the fitness effects of individual genetic diversity and suggest that metamorphosis and similar discrete life stage transitions may be critical periods of viability selection.

Individual growth rates and size at metamorphosis increase with watershed area in a stream salamander - Madaline M. Cochrane; Brett R. Addis; Leah K. Swartz; Winsor H. Lowe (Ecology, 2024)
A fundamental goal of ecology is to understand how the physical environment influences intraspecific variability in life history and, consequently, fitness. In streams, discharge and associated habitat conditions change along a continuum from intermittency to permanence: Headwater streams typically have smaller watersheds and are thus more prone to drying than higher‐order streams with larger watersheds and more consistent discharge. However, few empirical studies have assessed life history and associated population responses to this continuum in aquatic organisms. We tested the prediction that individual growth, rate of development, and population growth increase with watershed area in the long‐lived stream salamander Gyrinophilus porphyriticus , where we use watershed area as a proxy for hydrologic intermittence. To address this hypothesis, we used 8 years of mark–recapture data from 53 reaches across 10 headwater streams in New Hampshire, USA. Individual growth rates and mean size at metamorphosis increased with watershed area for watersheds from 0.12 to 1.66 km 2 . Population growth rates increased with watershed area; however, this result was not statistically significant at our sample size. Mean age of metamorphosis did not vary across watershed areas. Lower individual growth rates and smaller sizes at metamorphosis likely contributed to reduced lifetime fecundity and population growth in reaches with the smallest watershed areas and highest vulnerability to drought. These responses suggest that as droughts increase due to climate change, headwater specialists in hydrologically intermittent environments will experience a reduction in fitness due to smaller body sizes or other growth‐related mechanisms.

Source–sink dynamics within a complex life history - Winsor H. Lowe; Brett R. Addis; Madaline M. Cochrane; Leah K. Swartz (Ecology, 2023)
Source–sink patch dynamics occur when movement from sources stabilizes sinks by compensating for low local vital rates. The mechanisms underlying source–sink dynamics may be complicated in species that undergo transitions between discrete life stages, particularly when stages have overlapping habitat requirements and similar movement abilities. In these species, for example, the demographic effects of movement by one stage may augment or offset the effects of movement by another stage. We used a stream salamander system to investigate patch dynamics within this form of complex life history. Specifically, we tested the hypothesis that the salamander Gyrinophilus porphyriticus experiences source–sink dynamics in riffles and pools, the dominant geomorphic patch types in headwater streams. We estimated stage‐specific survival probabilities in riffles and pools and stage‐specific movement probabilities between the two patch types using 8 years of capture–recapture data on 4491 individuals, including premetamorphic larvae and postmetamorphic adults. We then incorporated survival and movement probabilities into a stage‐structured, two‐patch model to determine the demographic interactions between riffles and pools. Monthly survival probabilities of both stages were higher in pools than in riffles. Larvae were more likely to move from riffles to pools, but adults were more likely to move from pools to riffles, despite experiencing much lower survival in riffles. In simulations, eliminating interpatch movements by both stages indicated that riffles are sinks that rely on immigration from pools for stability. Allowing only larvae to move stabilized both patch types, but allowing only adults to move destabilized pools due to the demographic cost of adult emigration. These results indicated that larval movement not only stabilizes riffles, but also offsets the destabilizing effects of maladaptive adult movement. Similar patch dynamics may emerge in any structured population in which movement and local vital rates differ by age, size, or stage. Addressing these forms of internal demographic structure in patch dynamics analyses will help to refine and advance general understanding of spatial ecology.

Alterations of endophytic microbial community function in Spartina alterniflora as a result of crude oil exposure - Samantha D. Addis; Stephen K. Formel; Yeon Ji Kim; Paige B. Varner; Daniel B. Raudabaugh; Emilie Lefevre; Brittany M. Bernik; Vijaikrishnah Elango; Sunshine A. Van Bael; John H. Pardue; Claudia K. Gunsch (Biodegradation, 2022)

Long‐term survival probability, not current habitat quality, predicts dispersal distance in a stream salamander - Brett R. Addis; Winsor H. Lowe (Ecology, 2020)
Dispersal evolves as an adaptive mechanism to optimize individual fitness across the landscape. Specifically, dispersal represents a mechanism to escape fitness costs resulting from changes in environmental conditions. Decades of empirical work suggest that individuals use local habitat cues to make movement decisions, but theory predicts that dispersal can also evolve as a fixed trait, independent of local conditions, in environments characterized by a history of stochastic spatiotemporal variation. Until now, however, both conditional and fixed models of dispersal evolution have primarily been evaluated using emigration data (stay vs. leave), and not dispersal distances: a more comprehensive measure of dispersal. Our goal was to test whether conditional or fixed models of dispersal evolution predict variation in dispersal distance in the stream salamander Gyrinophilus porphyriticus. We quantified variation in habitat conditions using measures of salamander performance from 4 yr of spatially explicit, capture–mark–recapture (CMR) data across three headwater streams in the Hubbard Brook Experimental Forest in central New Hampshire, USA. We used body condition as an index of local habitat quality that individuals may use to make dispersal decisions, and survival probability estimated from multistate CMR models as an index of mortality risk resulting from the long‐term history of environmental variation. We found that dispersal distances increased with declining survival probability, indicating that salamanders disperse further in risky environments. Dispersal distances were unrelated to spatial variation in body condition, suggesting that salamanders do not base dispersal distance decisions on local habitat quality. Our study provides the first empirical support for fixed models of dispersal evolution, which predict that dispersal evolves in response to a history of spatiotemporal environmental variation, rather than as a conditional response to current habitat conditions. More broadly, this study underscores the value of assessing alternative scales of environmental variation to gain a more complete and balanced understanding of dispersal evolution.

Matching habitat choice and plasticity contribute to phenotype–environment covariation in a stream salamander - Winsor H. Lowe; Brett R. Addis (Ecology, 2019)
Populations optimize the match of phenotype to environment by localized natural selection, adaptive phenotypic plasticity, and habitat choice. Habitat choice may also be achieved by several mechanisms, including matching habitat choice, where individuals distribute themselves based on self‐assessment of the phenotype–environment match. Matching habitat choice is a relatively untested concept, but one that could advance our understanding of the interplay of movement ecology and intraspecific phenotypic variation. Morphology of the salamander Gyrinophilus porphyriticus differs in riffles and pools, the dominant habitats in headwater streams where this species occurs. Specifically, individuals found in riffles have shorter limbs than those found in pools. Here, we used 4 yr of spatially explicit capture–mark–recapture data from three streams to test the contributions of phenotypic plasticity and matching habitat choice to this phenotype–environment covariation. We quantified morphological variation in G. porphyriticus with size‐corrected principal component ( PC ) scores and assessed phenotype–environment match based on the difference between habitats in these PC scores. We found that both phenotypic plasticity and matching habitat choice contribute to phenotype–environment covariation in G. porphyriticus . The phenotypes of individuals that switched habitats (i.e., riffle→pool, pool→riffle) changed to become better matched to the recipient habitat, indicating a plastic response to local habitat conditions. Consistent with matching habitat choice, individuals were also more likely to switch habitats if their initial phenotype was a better match to the alternative habitat, independent of subsequent changes in morphology due to plasticity. Realized performance, survival adjusted for the likelihood of remaining in each habitat, was higher in individuals with phenotypes matched to each habitat than in those with mismatched phenotypes, but performance was generally lower in riffles than pools, suggesting that other factors influence the use of riffles. Our results underscore the value of considering how matching habitat choice interacts with other mechanisms that allow organisms to maximize performance when faced with environmental heterogeneity. More broadly, our study shows that it is important to account for movement in any study of the causes or consequences of intraspecific trait variation, a challenge that may require novel research approaches and experimental designs.

Population genetic structure and disease in montane boreal toads: more heterozygous individuals are more likely to be infected with amphibian chytrid - Brett R. Addis; Winsor H. Lowe; Blake R. Hossack; Fred W. Allendorf (Conservation Genetics, 2015)

Mitochondrial DNA variability of the pipefish Syngnathus abaster - D. Sanna; F. Biagi; H. B. Alaya; F. Maltagliati; A. Addis; A. Romero; J. De Juan; J.‐P. Quignard; A. Castelli; P. Franzoi; P. Torricelli; M. Casu; et al. (Journal of Fish Biology, 2013)
This study provides data on the genetic structuring of the pipefish Syngnathus abaster in the western Mediterranean and Adriatic Seas. A total of 109 specimens were collected in brackish‐water biotopes. The control region and three other regions of the mitochondrial genome were analysed. The most relevant result was the high genetic structuring found by Bayesian inference ( BI ), maximum likelihood ( ML ) and network analyses, which were consistent in showing three well‐separated clusters of S. abaster populations. Furthermore, BI and ML did not support the monophyly of the taxon S. abaster . These results suggest the occurrence of a species complex in the study area, whose differentiation may have occurred since the Pleistocene. The results also show a very high genetic variability at the inter‐population level, with no shared haplotypes among sites. Evolutionary forces due to the fragmented nature of the brackish‐water habitats may account for the high genetic divergence found among the groups and populations. Finally, although dispersal by rafting over long distances may occasionally occur, this study suggests linear stepping‐stone model of colonization to be most likely. The complexity of the results obtained suggests that further studies are needed to elucidate the phylogeny of S. abaster .